Use of X-Ray Computed Tomography (CT) in UK Sheep Production and Breeding - Bünger, L.; Macfarlane, J.M.; Lambe, N. R.; Conington, J.; McLean, K. A.; Moore, K.; Glasbey, C.A.; Simm, G. (IntechOpen, 2011)
None